Water‐dispersible nanocolloids and higher temperatures promote the release of carbon from riparian soil. Issue 1 (28th October 2020) - Rod, Kenton A.; Smith, A. Peyton; Leng, Weinan; Colby, Sean; Kukkadapu, Ravi K.; Bowden, Mark; Qafoku, Odeta; Um, Wooyong; Hochella, Michael F.; Bailey, Vanessa L.; Renslow, Ryan S.
Abstract: Increasing temperatures in alpine regions accompanied by glacial retreat is occurring rapidly due to climate change. This may affect riparian soils by increasing weathering rates, resulting in greater organic carbon (OC) release to rivers via movement of iron‐containing colloids and nanominerals. Increased concentrations of iron‐ or silcate‐nanominerals would result in higher surface area for OC adsorption. To test the influence of temperature on OC leaching, we examined mineral weathering and nanocolloid facilitated release of OC through a series of controlled laboratory batch and column experiments using sediment from the banks of the Nisqually River, Mount Rainier in Washington State (USA). Additional experiments were conducted using the same sediments, but with an illite amendment added to test the influence of additional surface area and nanominerals that many sediments along the Nisqually River contain. These higher‐ and lower‐surface‐area sediments (i.e., sediments with and without the illite amendment) were incubated for 90 d at 4 or 20 °C, followed by batch and column OC leaching tests. Results show that OC leaching rates for 20 °C were two to three times greater than for 4 °C. Further, our results suggest that nanocolloids are responsible for moving this increased OC load from these sediments. When hydrologically connected, OC is released from bank sediments to rivers faster than presently anticipated in fluvial environments experiencing climate change‐induced glacial retreat. Further, a one‐dimensional, finite‐element computational model developed for this study estimates that a 1 °C increase in temperature over a 90‐d summer runoff period increases the OC release rate from sediments by 79%. Core Ideas: Mineral nanocolloids protect and facilitate transport of soil organic carbon. Higher sediment specific surface area increases release of organic carbon with nanominerals. From our model, a 1 °C rise in the temperature increases the OC release rate up to 79% over 90 d.